Tourism strategy management in an effort to increase regional income and community economic resilience by the tourism, youth and sports office of Ngawi Regency - Mala, Istiana Wijayanti; Misnan, Misnan; Sutawa, Sutawa; Anwar, Khoyrul (Institute of Computer Science (IOCS), 2024)
Ngawi Regency has interesting and diverse tourism potential. However, Covid-19 has hampered tourism development and economic growth. Diparpora Ngawi Regency is trying to create a strategy in the tourism sector to increase the number of tourists again and have a good impact on increasing regional income and community economic resilience. This research focuses on Tawun Tourism Park because it is a legendary tour and offers more attractions. This research aims to examine tourism strategy management using the theory of strategic management stages, namely: strategy formulation, strategy implementation, and strategy evaluation. This research uses descriptive qualitative methods with data collection techniques through: interviews, documentation, and observation. The results showed that the strategy formulation was good because it was prepared based on the analysis of internal and external strengths and weaknesses. In the implementation of the strategy, the human resources of tourism managers are given training and coaching to be more skilled in conducting promotions, utilization of information technology and media is quite good. In the evaluation of the strategy, the results obtained an increase in the number of tourists who gradually improved and had an impact on increasing regional income and the economic resilience of the surrounding community.